Study of the volatile and glycosidically bound compounds of minority Vitis vinifera red cultivars from NW Spain - Canosa, P. (2011)
Aroma composition was analyzed in grape musts from five Vitis vinifera red cultivars (Pedral, Sousón, Caíño Redondo, Espadeiro and Mencía) grown in Galicia (NW Spain) with the aim to know the potential profile of these varieties. All cultivars were collected from Coto Redondo Winery vineyard (A.O.C. Rías Baixas) and grown under the same conditions. All cultivars (with a total of 96 aroma compounds, 35 free volatile and 61 glycosidically bound compounds) were identified and quantified by GC-MS. The results showed that Caíño Redondo and Pedral had the highest concentrations of volatile compounds. The free fraction showed the highest concentration for all cultivars studied with the exception of Pedral. High concentrations of free C6-compounds and free alcohols were found for all red cultivars studied, especially for Caíño Redondo. Sousón and Mencía presented similar characteristics in the free fraction. Pedral showed an important contribution of glycosidically bound compounds. This cultivar showed the highest concentration of bound alcohols, terpenoids, volatile phenols, and C13-norisoprenoids. With terpenoids, higher levels were found in the bound fraction than in the free fraction. Regarding C13-norisoprenoids, Pedral also showed an important contribution of these varietal compounds. The principal component analysis (PCA) showed a good separation of the different grape cultivars, so they could be discriminated based on their potential volatile composition. The oenological potential of ancient and minority grape varieties from NW Spain, with the aim to provide genetic diversity, is illustrated with this work.